Combatendo a ignorância, garantindo a ordem pública e o progresso da nação: ideias e ações educacionais de Francisco Mendes Pimentel (Minas Gerais, 1893-1910) - Carolina Mostaro Neves da Silva (2010)
We have investigated in this work the trajectory of the jurist, professor, journalist and politician Francisco Mendes Pimentel, detaching his actions and educational thoughts in Minas Gerais between 1893 and 1910. We have tried to articulate his actions and thoughts to the national and state political life, to the public instruction situation in Minas Gerais, to the press movement and to the ideas and initiative repertoire shared by politicians and public men at that time. Among some educational themes which Mendes Pimentel got involved, we detach the relation between public instruction dissemination and the Republic consolidation, the importance of the good preparation for teachers and the improvement for the teaching career and professional teaching destined to the less favored classes. The main sources we used were newspapers where Mendes Pimentel published his texts about education, the legal documents about public instruction in Minas Gerais and Annals from the Minas Gerais Congress. We have concluded that Mendes Pimentel effectively acted on debates about education, being coherent with the defense of republican principles and used the common repertoire of public men of his time in order to defend a public instruction able to make the republican citizen on arts and science, loving the nation and work.